Acercamiento criminológico al estudio de la Delincuencia Económica en Granma - Cuba (2016)
In this research, we propose to analyze the economic crime and the different theories andconcepts that from criminology have been made about this subject. As we will see, economiccrimes are not sociological or criminological basis in the reasons given to the traditional economiccrime from the criminological point of view. These crimes, also called of “cuello blanco”, havecertain characteristics that differentiate them from the rest of the crime and the perpetrators donot respond to the usual pattern of the offender. So our principal objective is to characterizethe economic crime in the current Cuban society, based on sociological studies conductedby various institutions in this regard. Under scientific problem that motivates, defined by thefollowing question: What are the main characteristics that presents economic crime in Cubansociety? Using for this purpose the following methods: Method of Analysis and Synthesis, LogicalAnalysis, Historical Legal, Sociological Method, Materialistic Dialectical Method. As researchtechnique was used the literature review of materials we consider more updated on the subject.Presenting results in a fundamental characterization of the phenomenon of economic crime fromthe criminological point of view.